Reformas en cuanto a fijar un porcentaje mínimo de trabajadoras en las relaciones laborales - Jami Minta, Luis Gerardo (2015)
Traditionally, women have always been able to intervene much less time in their professional life than men, by the existence of deep-rooted social customs still constitute one of the main obstacles women to be able to function professionally in the workforce is, but but in recent years much they have changed in terms of participation of women in the workforce. To achieve these objectives have generated determinants such as marriages to older and not as it was in ancient times the women they married at an early age, planning maternity independence in the sphere of the couple, increased domestic technology, increased personal services such as domestic services, nurseries and others, increased household consumption and longer life expectancy in women. These changes indicated, have been decisive actions to the evolution of the female gender in society in recent years, on the role of women at work, incidence of greater availability of time by women and their economic independence, labor, among others, all these changes have been the result of a socio-economic transformation, and the way of living and seeing the world, which has led to a change in the mentality of people, these economic and social changes have improved quality of life and led to an increase in consumption of women in the workplace. With the passage of time creating a new middle class with a lifestyle that can not be maintained only with the salary man, he has forced women to acquire training and professional qualifications for access to a job, and it has sought to be at a high level of competitiveness with men